2019
DOI: 10.1038/s41388-019-0786-6
|View full text |Cite
|
Sign up to set email alerts
|

Quaking orchestrates a post-transcriptional regulatory network of endothelial cell cycle progression critical to angiogenesis and metastasis

Abstract: Angiogenesis is critical to cancer development and metastasis. However, anti-angiogenic agents have only had modest therapeutic success, partly due to an incomplete understanding of tumor endothelial cell (EC) biology. We previously reported that the microRNA (miR)-200 family inhibits metastasis through regulation of tumor angiogenesis, but the underlying molecular mechanisms are poorly characterized. Here, using integrated bioinformatics approaches, we identified the RNA-binding protein (RBP) quaking (QKI) as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…Overall, 16 articles were identified and screened. After removal of 2 irrelevant studies [38,39] and 1 non-eligible article [37], 13 articles were considered eligible for our study [40][41][42][43][44][45][46][47][48][49][50][51][52]. A thorough search in ClinicalTrials.gov (access date on 1 January 2021) for additional studies retrieved no eligible studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, 16 articles were identified and screened. After removal of 2 irrelevant studies [38,39] and 1 non-eligible article [37], 13 articles were considered eligible for our study [40][41][42][43][44][45][46][47][48][49][50][51][52]. A thorough search in ClinicalTrials.gov (access date on 1 January 2021) for additional studies retrieved no eligible studies.…”
Section: Resultsmentioning
confidence: 99%
“…miR-200b was shown to negatively regulate the expression of quaking (QKI), an RNA-binding protein that implicates in endothelial maturation and proliferation. Overexpression of miR-200b inhibited tumor angiogenesis through downregulation of QKI in tumor endothelium [50]. Subsequently, QKI was shown to directly bind to and stabilize cyclin D1 (CCND1) mRNA.…”
Section: Othersmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA binding proteins (RBPs), the main undertaker of post-transcriptional regulatory process, are critical in RNA fate determination via regulating RNA splicing, nuclear export, degradation, stabilization and translation [3] . Recently, RBPs has been implicated as a critical regulator of an important series of cancer-related genes [4][5][6] . The dysregulation of RBPs has been shown to impact HCC carcinogenesis and progression [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…It plays an important regulatory role in accumulating ECs and to induce angiogenesis. Azam SH et al found that endothelial QKI‐5 expression remarkably correlated with angiogenic indices 21 . Cochrane A et al found that the mouse ECs overexpressing QKI‐5 significantly improved angiogenesis and neovascularization and blood flow recovery in experimental hind limb ischaemia.…”
Section: Introductionmentioning
confidence: 99%